Two decades of the gonococcal antimicrobial surveillance program in South America and the Caribbean: challenges and opportunities. (15th November 2013) - Dillon, Jo-Anne R; Trecker, Molly A; Thakur, Sidharath Dev; ,
Abstract : Objectives: The WHO has called for a global action plan to control the spread and impact of antibiotic resistant Neisseria gonorrhoeae . We report on key antimicrobial susceptibility (AMS) trends in countries in Latin America and the Caribbean from 1990 to 2011. Methods: Data collected between 1990 and 2011 by up to 23 countries in the Latin American and Caribbean region were aggregated and analysed for overall trends in N gonorrhoeae AMS to six antibiotics. Methods for gonococcal identification, susceptibility testing and interpretation were standardised. Results: More than 21 500 N gonorrhoeae isolates were tested for AMS between 1990 and 2011. The number of countries reporting yearly declined from 17 in the 1990s to 7 in 2011. The first isolates (0.4%, 20/5171) with reduced susceptibility (minimum inhibitory concentration ≥0.125 mg/L) to ceftriaxone were reported between 2007 and 2011. Ciprofloxacin resistance, first noted in the mid-1990s, ranged from 1.6% of isolates tested in 1997 rising to 42.1% in 2010. Overall, azithromycin resistance reached a high of 25.8% of isolates tested in 2008 falling to 1.0% in 2010. Resistance to penicillin ranged between 24.2% in 2003 to a high of 48.5% in 1993. Tetracycline resistance ranged between a high of 61.1% of isolates tested in 2001 to 21.8% in 2010. Plasmid mediated penicillin and tetracycline resistance declined over the period. Conclusions: Gonococcal AMS surveillance initiatives are urgently needed in every country in the region to ensure that effective treatments for gonococcal infections are in place and to better understand emerging trends in gonococcal antimicrobial resistance.